CHARACTERISTICS OF CONTINUITY TYPE SUPPORTED BY JENTIK Aedes aegypti IN REGIONAL WORKING PUSKESMAS BULILI - Budiman Budiman; Hamidah Hamidah (Promotif : Jurnal Kesehatan Masyarakat, 2017)
Dengue Hemorrhagic Fever (DHF) is a severe and potentially lethal dengue virus infection. DHF control measures can be performed on adult mosquitoes or in larvae. Controlling the larval stage can be done by cutting the chain of transmission of dengue disease through containers that made Aedes aegypti mosquitoes laying and breeding. This study aims to determine the preferred container characteristics of larva Aedes aegypti in the work area of Puskesmas Bulili, South Palu District. This research will be carried out in the work area of Puskes Puskesmas Public Health Center by using spot survey method by observing all containers potentially become Aedes aegypti larvae breeding place in research location. The variables under study will be presented in descriptive form by describing the environmental characteristics of containers preferred by Aedes aegypti mosquito larvae ranging from type, base material and container location. The results showed that the type of container favored by Aedes aegypti mosquitoes is the type of bathtub with a base material made of plastic and the location of the container inside the community house.Keywords : DHF, Container, Aedes aegypti